A Special Issue on Microorganisms from Extreme Environments in Memory of Luigi Michaud (1974–2014) - Angelina Lo Giudice; Concetta Gugliandolo (Diversity, 2019)
A special issue (SI) titled “Microbial Diversity in Extreme Environments: Implications for Ecological and Applicative Perspectives” has been launched with the aim of showcasing the diversity and biotechnological potential of extremophilic microorganisms. The issue includes 10 research papers and four reviews that mainly address prokaryotes inhabiting hyperarid, hypercold, hyperalkaline and hypersaline (or polyextreme) environments, spanning from deserts to meromictic and glacier lakes around the globe. Thermophilic prokaryotes from shallow hydrothermal vents and Antarctic geothermal soils are also treated. The ecology and biotechnological perspectives of eukaryotes are discussed in two review papers and one research paper. This special issue serves as a memorial to Dr. Luigi Michaud (1974–2014), who dramatically passed away in Antarctica during underwater sampling activities.